Increasing payload capacity of wearable robots employing linear actuators and elastic mechanism - Choo, Junghoon; Park, Jong Hyeon (International journal of precision engineering and manufacturing, 2017)
In military and industrial applications, wearable robots should meet the required payload capacity in all human motion range owing to dealing with heavy loads, which is safety and work performance issues. But, the payload capacity of wearable robots employing linear actuators gradually decreases while the pilot bends his knees with a stand-to-sit motion, because the moment arm of actuating force varies and decreases drastically. To deal with this issue, this study proposes an elastic mechanism combined with a sub-link mechanism to increase the moment arm of the elastic force in the knee-flexion posture. This mechanism generates additional torque to supplement the force needed during sit-to-stand and stand-to-sit motions with heavy loads. The proposed mechanism was simulated and tested with a wearable robot, and its effectiveness was verified.